Analisis Tingkat Kebisingan di Sekitar Lokasi Penambangan Bijih Nikel: (Studi Kasus di Kecamatan Langgikima Kabupaten Konawe Utara) - Abriansyah, Abriansyah; Putra, Adris Ade; Simatupang, Minson (Universitas Muhammadiyah Kendari, 2025)
Nickel mining activities play a significant role in driving regional economic development; however, they also pose considerable environmental challenges, one of which is noise pollution. This study aims to assess the ambient noise levels surrounding the nickel mining operations in Langgikima District, North Konawe Regency, and to evaluate their potential impacts on public health and environmental well-being. A field survey approach was employed, wherein noise measurements were conducted using a calibrated Sound Level Meter (SLM). Sound pressure levels in decibels A-weighted dB(A) were recorded over a ten-minute interval, with readings taken every five seconds. The data were then analyzed to determine the daytime noise level (Ls), based on four distinct measurement periods. The findings reveal that daytime noise levels in the residential area of Lameruru Village ranged around 53.3 dB(A), which remains below the residential noise threshold of 55 dB(A) as stipulated by the Indonesian Ministry of Environment Regulation No. 48/1996. Despite compliance with existing standards, these results underscore the need for enhanced noise management strategies to ensure long-term environmental quality and public health protection.